Systematic Market Risk Adjusted for Liquidity Cost in the Banking Sector - Hassanein, Medhat (Archives of Business Research, 2022)
The emergence of one or more risks in the financial markets during a specific period causes a financial crisis. Financial crises impact financial stability, which is a key concern for all financial authorities, including central banks. One way to mitigate the risks any economy faces is to understand the origin of risk and how it spreads through the financial system. Liquidity risk goes hand-in-hand with market risk, as they affect each other during a crisis. After the 2007-2008 global financial crisis, banks showed that they need monitoring and efficient liquidity management during both stress and normal conditions; that is, they require better integration of bank liquidity and market risk management. In this study, we present a new methodology to forecast the systematic market risk adjusted for liquidity cost based on the Conditional Value at Risk (CoVaR) risk measure and asymmetric conditional copulas. We analyze a sample of international banks based on asset size in the US, EU, and Asia. Our hypothesis confirms that liquidity risk goes hand-in-hand with market risk, as they affect each other during a crisis. The results show dependence in the tails of the banks’ returns and the market returns. These are very high generally, and even higher for the Covid-19 period than for other periods. The effect of both market risk and liquidity risk on banks during a crisis period is less than in non-crisis periods because banks are well informed institutions and can anticipate a financial crisis and mitigate risk, which explains our results.